IDENTIFIKASI GULMA DI LAHAN PERTANIAN HORTIKULTURA KECAMATAN TARAKAN UTARA KALIMANTAN UTARA - Aditya Murtilaksono; Muhammad Adiwena; Nurjanah Nurjanah; Abdul Rahim; Muhammad Syahil (FAKULTAS PERTANIAN UNIVERSITAS BORNEO TARAKAN, 2021)
AbstractTarakan is a city located in North Kalimantan Province. Tarakan City Has four Districts, namely East Tarakan District, West Tarakan District, East Tarakan District, and North Tarakan. District Residents of North Tarakan District with various kinds of occupations. One of the fields of work in North Tarakan District is Farmers. Every sub-district in North Tarakan District has a farmer group leader. One of the problems of farmers in North Tarakan District is their lack of knowledge about pests, disease and weeds. Pests, disease and weeds, assuming we do not control, will reduce agricultural yields of farmers. Weeds are plants that live on agricultural land and are detrimental to farmers because they have the ability to compete in agricultural land that does not have nutrients, sunlight and air on agricultural land. Therefore it is necessary to carry out weed investigations on farmers' land in Tarakan City so that it can support food security in North Tarakan District. Based on the results of weed investigations in North Tarakan District, it can be concluded that the highest weed found in North Tarakan District with an SDR value of 18.92% was Elusine indica and the lowest was found in North Tarakan District with an SDR value of 0.16% was Mikania micrantha weed, the total number Weeds identified were 29 weed species.Key words: identification, vegetables, vegetation, weed Abstrak Tarakan merupakan Kota yang terletak di Provinsi Kalimantan Utara. Kota Tarakan Memiliki empat Kecamatan yaitu Kecamatan Tarakan Timur, Kecamatan Tarakan Barat, Kecamatan Tarakan Timur, dan Kecamatan Tarakan Utara Penduduk Kecamatan Tarakan Utara dengan berbagai macam bidang pekerjaan. Salah satu bidang pekerjaan yang terdapat di Kecamatan Tarakan Utara adalah Petani. Setiap kelurahan di Kecamatan Tarakan Utara Memiliki Ketua Kelompok Tani. Salah satu permasalan petani yang terdapat di Kecamatan Tarakan Utara adalah kurangnya ilmu pengetahuan tentang hama, penyakit dan gulma. Hama, penyakit dan gulma apabila kita tidak dikendalikan akan menurunkan hasil pertanian petani. Gulma adalah tumbuhan yang hidup di lahan pertanian dan bersifat merugikan bagi petani karena memiliki kemampuan untuk bersaing dalam perebutan unsur hara, cahaya matahari dan air di lahan pertanian. Oleh karena itu perlu dilakukan penelitian identifikasi gulma pada lahan petani di Kota Tarakan sehingga dapat mendukung ketahanan pangan di Kecamatan Tarakan Utara. Berdasarkan hasil penelitian identifikasi gulma di Kecamatan Tarakan Utara dapat disimpulkan gulma yang paling tinggi didapatkan di Kecamatan Tarakan Utara dengan Nilai SDR 18.92% adalah gulma Elusine indica dan gulma yang paling rendah didapatkan di Kecamatan Tarakan Utara dengan Nilai SDR 0.16% adalah gulma Mikania micrantha, jumlah total gulma yang teridentifikasi adalah 29 spesies gulma.